Bacteriocin and its Current Application as a Food Packaging Film Component against Spoilage: A Narrative Review - Sanguyo, France Heather C.; Angeles, Felliah Lou A.; Deborde, Shena Marice V.; Jumarang, Khristine C.; Mahait, Jean Angelique; Onayan, Rio Sarah M.; Pacada, Marla Jermaine V.; Pitong, Carmela R.; Hagosojos, Bernardino M. (Asian Journal of Biological and Life Sciences)
Food spoilage still concerns the manufacturing of food products. Several factors contributed to this problem, including temperature during preservation or storage, moisture and water content, and the majority are due to bacteria that cause spoilage. Lactic Acid Bacteria (LAB) have several uses, including as either starter cultures or probiotics due to their antimicrobial compounds. LAB produce bacteriocins, which have a significant role in biopreservation. The incorporation of bacteriocins into different packaging films has proven to control the spoilage bacteria growth and at the same time improve food quality. However, the Food and Drug Administration (FDA) has only approved a few LAB bacteriocins as biopreservatives, wherein nisin is the most popular. Packaging immobilization of other bacteriocins that have a broader antimicrobial scope has become an interest. This narrative review discusses the current applications of bacteriocins as food packaging film components against spoilage. A total of 20 studies were retrieved from PubMed, GoogleScholar, ScienceDirect, and ResearchGate, restricting from 2013-2021. The gathered literature works reported novel bacteriocins that can be candidates as biopreservatives due to their broader antimicrobial scope and inhibitory effects. However, there is still a need for further investigation of the newly discovered LAB bacteriocins on their packaging application and inhibition of food pathogens.
Keywords: Antimicrobial packaging; Bacteriocins; Biopreservation; Food packaging; Lactic acid bacteria; Spoilage